Resveratrol, curcumin and gallic acid attenuate glyoxal-induced damage to rat renal cells - Mahmoud Hashemzaei; Kaveh Tabrizian; Zeinab Alizadeh; Sedigheh Pasandideh; Ramin Rezaee; Charalampos Mamoulakis; Aristidis Tsatsakis; Zoi Skaperda; Demetrios Kouretas; Jafar Shahraki (Toxicology Reports, 2020)
Glyoxal (GO), a by-product of glucose auto-oxidation, is involved in the glycation of proteins/ lipids and formation of advanced glycation (AGE) and lipoxidation (ALE) end products. AGE/ALE were shown to contribute to diabetic complications development/progression such as nephropathy. Diabetic nephropathy progression has an oxidative nature. Given the antioxidant effects of polyphenols, potential protective effects of resveratrol, curcumin and gallic acid, in rat renal cells treated with GO, were evaluated in the present work. According to our results, incubation of GO with the cells reduced their viability and led to membrane lysis, reactive oxygen species (ROS) formation, lipid peroxidation, mitochondrial membrane potential collapse, and lysosomal membrane leakage. These findings were prevented by pre-treatment with resveratrol, curcumin and gallic acid. Mitochondrial and lysosomal toxic interactions appear to worsen oxidative stress/cytotoxicity produced by GO. Resveratrol, curcumin and gallic acid inhibited ROS formation and attenuated GO-induced renal cell death.